Clinical characteristics, imaging features, and fate of punctate outer retinal toxoplasmosis lesions in immunocompetent cases of ocular toxoplasmosis - Kelgaonkar, Anup; Jadhav, Vishal; Patel, Anamika; Basu, Soumyava; Pathengay, Avinash (Taiwan journal of ophthalmology, 2025)
PURPOSE: The purpose of this study was to study clinical characteristics, imaging features, and fate of punctate outer retinal toxoplasmosis (PORT). MATERIALS AND METHODS: A retrospective, observational, descriptive analysis of PORT lesions presenting as satellite lesions of typical full-thickness necrotizing Toxoplasma retinochoroiditis (TRC) or isolated lesions in immunocompetent cases. RESULTS: We analyzed 34 eyes of 34 cases (22 males and 12 females). PORT lesions appeared as deep, dull, yellowish-gray outer retinal lesions, either as satellite lesions to a TRC (n = 30) or isolated macular punctate lesions (n = 4). The mean lesion size was 562 μm (50-1000). The recurrence rate was high (23.52%), manifesting as either typical TRC (n = 4) or new satellite PORT lesions (n = 4). Active lesions had hyperreflective outer retinal foci on optical coherence tomography (OCT), hyperautofluorescent in the active phase, and stippled upon resolution. Healed lesions exhibited outer nuclear layer thinning and outer retinal atrophy on OCT and were hypoautofluorescent. CONCLUSION: PORT lesions were observed as multiple punctate lesions, either adjacent to TRC in active or healed phases or as isolated macular punctate toxoplasmosis. Autofluorescence, angiography, and OCT assist in differentiating active from healed lesions. The fate of PORT lesions was healing with granularity, fading, or complete resolution. Some cases recurred with new satellite PORT lesions, whereas others progressed to typical retinochoroiditis or CNVM.